Psicodinâmica do trabalho: vivências de prazer e sofrimento de trabalhadores com deficiência no ambiente hospitalar - Diniz, Fernanda Alexandre (2022)
The historical trajectory of people with disabilities was marked by moments of segregation and social exclusion, however these conceptions were modified over time, which enabled more dignified living conditions, integrating them into society. The creation of affirmative action policies enabled the inclusion of these people in the labor market. In this context, this research, of a qualitative nature based on a descriptive analysis, aimed to know how the experiences and meanings produced by workers with disabilities who work in a private hospital are in relation to the reality of work, how the experiences of pleasure and suffering, which defensive strategies were developed and how the health-disease process occurs. For this purpose, a semi-structured interview was applied to ten workers with disabilities, whose results were compiled using the Analysis of the Nuclei of Senses (ANS) technique, the information was allocated into axes, categories, themes and frequency of responses in relational mode (n=>N) organized in tables, the psychodynamics of work theory was used for analysis. It was concluded that, for workers with disabilities, the positive experiences arising from work generate pleasure, due to the symbolic rewards caused by the act of working. Reinforcing the construction of identity, enabling interaction outside the family environment, increasing their social circle, giving them a sense of belonging, of social integration. In addition, work enables access to service and consumer goods, developing their autonomy, demystifying the stigmas and stereotypes of incapacity and invalidity. However, it was observed that the organization of work has factors that lead some workers with disabilities to report having a greater effort to perform the task, giving them a feeling of impotence, which may result in suffering, physical and psychological exhaustion, compromising the health, well-being and safety of these workers, sometimes some individual defense strategies are observed, such as reports of submission and adaptation behavior to work in inadequate conditions due to lack of accessibility, being resilient and overcoming limitations in the face of happenings. It is generally suggested that companies institute policies and collective spaces that discuss the universe of workers with disabilities, enabling work environments that are accessible and adapted to their needs, providing a healthy and humanized environment that meets current legislation.